A model of tropical storm from temperature anomaly distributions (MAUSAM, 1988)
A simple equation has been formulated to find out the temperature anomaly distributions in axisymmetric steady state tropical storm from a few known values in the real storm and a method to find out the velocity and pressure distributions of storm from it. A. few case studies with assumed typical distribution of anomaly field have been discussed. It has been found that In addition to horizontal distribution of anomaly field, strength of the storm depends on its vertical distribution also. Profiles relating to the maximum temperature anomaly with maximum tangential velocity and that with minimum sea level pressure are also presented which have good agreement with typical real storms and can be readily used as a nonogram.